Brucella melitensis Rev.1 live attenuated Vaccine and its DNA induced IFN- γ and anti-ds DNA antibodies production in rats - Utba, Nawal; Qays, Raghad (Iraqi Journal of Science, 2023)
Brucellosis is one of the five common bacterial zoonoses in the world caused byorganisms belonging to the genus Brucella. Immune recognition of bacterialinfection may contribute to cytokine, as well as antibody production that arecharacteristic of innate and adaptive responses. In this study, the presence ofattenuated live Brucella melitenses Rev1 bacteria or its DNA induced the immunesystem to produce IFN-γ and anti-ds DNA antibody. In respect to IFN-γ released,the B. melitensis Rev 1 attenuated live vaccine was able to stimulate the immunesystem more than the DNA (P≤0.05). Such finding could be attributed to the wholeattenuated bacteria that have immunogenic factors other than the DNA like cell wallcomponent and outer membrane. On the other hand, the B. meliensis Rev 1 DNAactivated the B cell to secret anti-ds DNA antibodies significantly higher (P≤ 0.05)than live attenuated vaccine, and the level of antibodies was increased to parallel theconcentration increases of injected DNA.